VOICE TO THE VOICELESS: A RESISTANCE STUDY IN THE SELECT NOVELS OF BARBARA KINGSOLVER - Sujitha S. K; Bose, A. Xavier Chandra (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Resistance encompasses each and every action of opposition, defiance, and protest for reclaiming the justice. Power, resistance and justice are tangled in the life of common people. This paper aims to focuses on the resisting power of people, especially women against the tyrannical power structure in order to protect their land, environment and livelihoods which are under the verge of exploitation. By introspecting the selected novels, Animal Dreams, Prodigal Summer and Flight Behaviour, this study explores the voice of resistance echoed behind the narratives of Barbara Kingsolver. The voices of suppressed may not be heard often, but that doesn’t mean they are voiceless. They speak at the right platform of protest through necessary actions.